Studi Perbandingan Produktivitas Teori dan Realitas pada Pekerjaan Konstruksi Keselamatan Pesisir di Teluk Jakarta Tahap 6 Paket 4 - Widhitomo, Kurniawan; Azhar, Moh; Mardiaman, Mardiaman (Universitas Batanghari Jambi, 2025)
Coastal protection infrastructure in Jakarta Bay is essential to mitigate flooding due to sea level rise and land subsidence. The use of spun piles with inner boring methods supported by Hydraulic Static Pile Driver (HSPD) technology is intended to ensure efficient and low-impact pile driving operations. However, in practice, productivity discrepancies between theoretical planning and field realization remain a significant issue. This study aims to analyze and compare theoretical productivity (based on contractual planning) with actual field productivity in the installation of spun piles for a coastal safety project in Jakarta Bay Phase 6 Package 4. A descriptive quantitative approach was used, combining direct field observations, time-lapse video analysis, and secondary data from contract documents. Productivity was measured in meters per hour (m/h) and piles per day (piles/day). Deviations between theoretical and actual productivity were identified, and causal factors were analyzed. Theoretical productivity was 3.59 m/h with 3.5 piles/day, while actual field productivity reached only 3.2 m/h with 3.33 piles/day. This discrepancy resulted in an estimated delay of 5 workdays (4.8% deviation). The primary contributing factors were inconsistent hydraulic pressure, environmental constraints, equipment limitations, and varying operator skill levels. The study confirms that real-time monitoring and productivity assessment tools are crucial for timely project delivery. It also highlights the need for adaptive planning and systematic operator training. The findings provide practical guidance for enhancing productivity in future coastal foundation projects using HSPD technology.